2018
DOI: 10.1021/acsnano.7b07572
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Peptide-Coated Ultrasmall Superparamagnetic Iron Oxide Nanoparticles for In Vivo Contrast-Enhanced Magnetic Resonance Imaging

Abstract: The biocompatibility and performance of reagents for in vivo contrast-enhanced magnetic resonance imaging (MRI) are essential for their translation to the clinic. The quality of the surface coating of nanoparticle-based MRI contrast agents, such as ultrasmall superparamagnetic iron oxide nanoparticles (USPIONs), is critical to ensure high colloidal stability in biological environments, improved magnetic performance, and dispersion in circulatory fluids and tissues. Herein, we report the design of a library of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 32 publications
(71 reference statements)
0
51
0
Order By: Relevance
“…To reduce toxicity, SPIONs are often coated with biocompatible polymers such as dextran, PEG, and PEI (Muthiah, Park, & Cho, 2013). There have also been attempts to encapsulate nanoparticles in lipids (H.-C. Huang et al, 2009;Liang, Zhang, Miao, Li, & Gan, 2017) and peptides (Chee et al, 2018) to reduce toxicity and improve circulation time. Others have also found that cytotoxicity is both coating-and size-dependent (Feng et al, 2018).…”
Section: Biological Interactions Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…To reduce toxicity, SPIONs are often coated with biocompatible polymers such as dextran, PEG, and PEI (Muthiah, Park, & Cho, 2013). There have also been attempts to encapsulate nanoparticles in lipids (H.-C. Huang et al, 2009;Liang, Zhang, Miao, Li, & Gan, 2017) and peptides (Chee et al, 2018) to reduce toxicity and improve circulation time. Others have also found that cytotoxicity is both coating-and size-dependent (Feng et al, 2018).…”
Section: Biological Interactions Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…Apart from polymeric coating (e.g., PEG, PEI, PAA), effective MRI contrast agents based on iron oxide NPs with different surface coatings have been reported in the literature. Previously, peptide coating has been shown to enhance the r 1 (2.4 m m −1 s −1 ) and r 2 relaxivities (217.8 m m −1 s −1 ) of ultrasmall SPIONs (USPIONs) with higher relaxivity ratios (>90) relative to commercially available MRI contrast agents . Furthermore, peptide‐coated USPIONs could show high contrast enhancement of the liver for detection of liver tumors.…”
Section: Functional Applications Of Iron Oxide‐based Nanoarchitecturesmentioning
confidence: 99%
“…Peptides and peptide derivatives have been extensively employed for constructing multifunctional nanotheranostics since they exhibit chemical versatility and enable to specically recognize other biomacromolecules. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] In particular, conjugation of nanoparticles with tumor-homing peptides and/or therapeutic peptides can generate novel nanotheranostics for highly sensitive tumor imaging and effective tumor-targeted therapy. For example, Ruoslahti and coauthors have been developed a theranostic nanosystem, which consists of iron oxide nanoworms conjugated with a composite peptide with proapoptotic domain (i.e., therapy motif) and cell surface p32 protein binding domain (i.e., tumor-homing motif).…”
Section: Introductionmentioning
confidence: 99%